2014
DOI: 10.1093/hmg/ddu136
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an antibody directed against Nogo-A delays disease progression in the SOD1G93A mouse model of Amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal, neurodegenerative disorder in which motor neurons in the spinal cord and motor cortex degenerate. Although the majority of ALS cases are sporadic, mutations in Cu-Zn superoxide dismutase-1 (SOD1) are causative for 10-20% of familial ALS (fALS), and recent findings show that a hexanucleotide repeat expansion in the C9ORF72 gene may account for >30% of fALS cases in Europe. SOD1(G93A) transgenic mice have a phenotype and pathology similar to human ALS. In both ALS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…sAPP-α binds to unphosphorlyated CRMP2 which may help maintain CRMP2 in an non-phosphorylated state and thus aid in the stabilization of the neuronal cytoskeleton. Neutralization strategies using antibodies directed toward NRP1 (Venkova et al, 2014) or NOGO-A (Bros-Facer et al, 2014) have the ability to inhibit these signaling pathways, probably by preventing phosphorylation of the appropriate CRMPs, and thus enhancing neuronal cytoskeleton stabilization. Fasudil, a RhoA-kinase inhibitor, can be administered to prevent EPHA4 function by inhibiting the activation of downstream mediators that usually lead to the destabilization of the neuronal cytoskeleton.…”
Section: Distinctive Axonal And/or Synaptic Features That Could Initimentioning
confidence: 99%
See 1 more Smart Citation
“…sAPP-α binds to unphosphorlyated CRMP2 which may help maintain CRMP2 in an non-phosphorylated state and thus aid in the stabilization of the neuronal cytoskeleton. Neutralization strategies using antibodies directed toward NRP1 (Venkova et al, 2014) or NOGO-A (Bros-Facer et al, 2014) have the ability to inhibit these signaling pathways, probably by preventing phosphorylation of the appropriate CRMPs, and thus enhancing neuronal cytoskeleton stabilization. Fasudil, a RhoA-kinase inhibitor, can be administered to prevent EPHA4 function by inhibiting the activation of downstream mediators that usually lead to the destabilization of the neuronal cytoskeleton.…”
Section: Distinctive Axonal And/or Synaptic Features That Could Initimentioning
confidence: 99%
“…NMJ destabilization by NOGO-A is consistent with the fact that NOGO-A signaling has been linked to synaptic plasticity and stability in hippocampal neurons (Peng et al, 2011) and in the adult cerebral cortex (Akbik et al, 2013). A recent study has illustrated the potential of anti-NOGO-A antibodies in significantly improving neuromuscular function even when administered to ALS mice in the symptomatic stages of the disease (Bros-Facer et al, 2014). Currently a Phase II trial is underway using anti-NOGO-A antibodies (GSK; Ozanezumab) in an effort to neutralize NOGO-A function in ALS patients (ClinicalTrials.gov: NCT01753076), with primary results due in May 2015.…”
Section: Molecular Mechanisms That Govern Distal Axon and Nmj Stabilimentioning
confidence: 99%
“…Skeletal muscles in mutant SOD1 mice evidence signs of hypermetabolism and oxidative stress even at asymptomatic stages of disease (reviewed in Cozzolino and Carri, 2012), and increase expression of Nogo-A, which inhibits formation of neuromuscular junctions (Bros-Facer et al, 2014). …”
Section: Why Does Knockout Of Cyclophilin D (Cypd) Preserve Motor Neumentioning
confidence: 99%
“…Mutations in the superoxide dismutase 1 gene (SOD1) account for 10–20% of all fALS cases. Recently, a hexanucleotide repeat expansion in the C9ORF72 gene was found to explain more than 50% of fALS cases [3, 4]. It has been shown that overexpression of the mutant human SOD1 gene in mice reproduces the ALS phenotype observed in humans [5].…”
Section: Introductionmentioning
confidence: 99%